Obtenção de filmes finos do sistema ZnO:Co depositados em substratos de vidro e safira via Spin Coating - Costa, Anderson Stojan (2014)
Co-Doped ZnO thin films, a diluted magnetic semiconductor with great potential to be used in the manufacture of spintronic devices, were prepared via Pechini method. Films with nominal concentrations of 1, 3 and 5 mols % of Co were depositions by spin-coating on glass and sapphire substrates. The prepared thin films were characterized by X-ray diffraction, scanning electron microscopy, EDS analysis and X-ray absorption. X-ray diffraction patterns indicated that the films doped with Co on the glass substrate has a crystalline phase with wurtzite structure. EXAFS spectra suggest that in thin films with concentrations of 5 mol% of Co, these atoms are not only occupying the Zn2 + ionic sites within the ZnO crystal lattice. The thicknesses of the films measured using images from scanning electron microscopy were between the values of 160 nm and 800 nm. The method and procedures employed in the work produced good films on glass substrates, thick and well distributed across the surface of the substrate one. The films deposited on sapphire substrates not uniformly covered the surface of the substrate.